2018
DOI: 10.4491/eer.2018.057
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of a regenerative thermal oxidizer for volatile organic compounds treatment

Abstract: As regulations governing the control of volatile organic compounds (VOCs) have become increasingly stringent in China, regenerative thermal oxidizers (RTOs) have been more frequently applied in medium-and high-concentration VOCs treatments. However, due to the lack of existing RTO-related research, experience remains a dominant factor for industrial application. This paper thus aimed to establish a model for industrial RTOs, using a transient simulation method and thermal equilibrium model to simulate the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…One major effect of the gas flow rate in such devices is on the residence time and gas velocity, which are important factors than can affect VOC conversion performance. Typical residence times for VOCs in industrial scale thermal oxidizers are between 0.5 s and 2 s. 25,26 Lewandowksi 26 describes that thermal oxidizers should be designed to have a non temperature corrected gas velocity between 6 m s −1 and 12.1 m s −1 . At a temperature of about 800 °C this would correspond to standard velocities of 1.7 m s −1 to 3.3 m s −1 , if the changed air density is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…One major effect of the gas flow rate in such devices is on the residence time and gas velocity, which are important factors than can affect VOC conversion performance. Typical residence times for VOCs in industrial scale thermal oxidizers are between 0.5 s and 2 s. 25,26 Lewandowksi 26 describes that thermal oxidizers should be designed to have a non temperature corrected gas velocity between 6 m s −1 and 12.1 m s −1 . At a temperature of about 800 °C this would correspond to standard velocities of 1.7 m s −1 to 3.3 m s −1 , if the changed air density is taken into account.…”
Section: Introductionmentioning
confidence: 99%
“…The lower residual color after oxidation with H2O2/O3 as the H2O2/O3 ratio increased was attributed to the increased formation of OH radicals [20][21][22][23]. Other studies have reported increased H2O2/O3 ratios and biodegradability after wastewater treatment with O3 and H2O2 [24,25].…”
Section: Optimization Of H2o2/o3 Ratiomentioning
confidence: 99%
“…During the past decades, many different methods for VOCs treatment have been developed and used in the industry, such as absorption, , oxidation, condensation, biological degradation, membrane separation, , and adsorption. The adsorption is a promising and efficient method for removal and recovery of VOCs .…”
Section: Introductionmentioning
confidence: 99%